Política econômica e dinâmica do ICMS: uma análise da economia cearense em perspectiva regional entre 2005 e 2013 - Cruz, Marco Aurélio Clemente da (2015)
This study aims to investigate the relationship between the state economic policy of Ceará vis à vis the other states of the Northeast, in line with developments of the collection of the Tax on Circulation of Goods and Interstate and Intermunicipal Transportation and Communication Services (ICMS). Data from state collections were obtained from the website of the National Council for Financial Policy (CONFAZ), from January/2005 to December/2013. The initial analysis of the correlations between the collections of the State of Ceará and the collections of other states of the Northeast showed an association around 95%, suggesting the occurrence of a set growth throughout the Northeast. Finally, he compared the evolution of the collection of Ceará the average collection of the northeastern states and unit root tests were performed ADF and KPSS to investigate its long-term trend. The results indicated the possibility of cointegration between the evolutions of Ceará State ICMS collection with most Northeastern states except the states of Piauí, Rio Grande do Norte and Alagoas. In addition, there is an increase in Ceará ICMS January/2009 to January/2010 above the regional average and an apparent cooling of this growth thereafter.